Bài Tổng quan: Phản ứng Michael chọn lọc lập thể của các enolat và ứng dụng trong tổng hợp hữu cơ† - Thuận, Ngô Thị; Tuấn, Đặng Thanh (Vietnam Journal of Chemistry, 2016)
Michael reaction of enolates is one of the most important C-C bond forming reactions in organic synthesis. Recent developments of chiral catalyst systems (metal catalysts and organocatalysts) allowed Michael reaction of enolates to be carried out under mild conditions giving desired addition products in high yield and enantioselectivity. In this review, several important aspects related to stereoselectivity and enantioselectivity are discussed in details. In addition, some practical applications of tandem Michael and asymmetric Michael reactions in the total synthesis of bioactive natural products, and pharmaceuticals were demonstrated.